(untitled) (Linguostylistic Studies, 2022)
This article considers the issue of compound adjectives usage in the poetry of Lesya Ukrainka. In the focus of the case study is their semantics, creation/formation, and functioning. The goal of the work is to characterize the semantics and derivational structure of compound adjectives in the poetry of Lesya Ukrainka, identify their productive word-forming types, consider the features of their functioning, and determine the aim of such adjectives’ usage in poetic works of the writer. The compound adjectives have been selected in terms of the semantic-grammatical approach and classified into several groups. The most numerous group involves the adjectives characterizing a person by his/her features (appearance, inner qualities, social status, religious preferences, etc.). The study has also identified adjectives that describe nature, flora, fauna, etc. Another representative group of compound adjectives used by Lesya Ukrainka in her poetry comprises adjectives that give general evaluative characteristics in combination with abstract nouns. These compound adjectives in the poetic discourse of Lesya Ukrainka perform emotionally-expressive role, reproducing the mental or emotional state of the heroes and their thoughts. The other group of compound adjectives concerns those with color semantics aimed at conveying shades of colors, their brightness, degree intensity, and color saturation. All compound adjectives revealed in Lesya Ukrainka’s poems are formed according to traditional word-formation models characteristic of the Ukrainian language. A number of individual author lexemes are highlighted with the description of their aesthetic role. The scientific research findings argue that in the poetry of Lesya Ukrainka, compound adjectives perform the emotionally expressive, evaluative, and characterizing role.